Urban Landscape Design Based on Virtual Reality Technology. (8th October 2022) - Li, Xiang; Guo, Yanan
Abstract : Different from the western classical stone buildings, China has formed the traditional architectural style with wood as the main body since ancient times. With the progress of the times and the collision between Chinese and western cultures, people put forward higher requirements for the current urban planning and landscape design, hoping that the future urban landscape design can follow the style of "Chinese and new." Traditional urban landscape design usually adopts solid model, rendering renderings, or three-dimensional animation, but these methods all have some defects. With the development of computer technology and the rise of Internet industry, virtual reality technology appears, and because of its excellent multiperception, immersion, interactivity, and autonomy, it is gradually applied to medical, military, entertainment, virtual city, and other fields of human life. Urban landscape design based on virtual reality technology is an important technical way of urban landscape design at present. It can help designers to better perfect the design details, experience it personally in the design process, find the existing problems and defects in the current design in time, and improve the design efficiency. It can also assist urban planners to make corresponding decisions. However, due to the high cost and the shortage of technical personnel, it is only implemented in a small area at present. Take the virtual Los Angeles project in the United States as an example, which is a typical case of the application of virtual reality technology in urban planning and construction and successfully realizes the interactive function between users and virtual environment. With the continuous development and improvement of virtual reality technology, there are more and more corresponding talents, and this technology will be widely used in the future urban planning and construction, forming our own "middle and new" urban landscape style.